2014
DOI: 10.1155/2014/475480
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Telmisartan Plus Amlodipine in Asian Patients Not Adequately Controlled on Either Monotherapy or on Low-Dose Combination Therapy

Abstract: Objective. To evaluate the efficacy and safety of the telmisartan plus amlodipine (T/A) single-pill combination (SPC) in Asian patients with hypertension whose blood pressure (BP) was not adequately controlled on either monotherapy or on low-dose combination therapy. Patients and Methods. Data are presented from five Boehringer Ingelheim-sponsored phase 3, double-blind, 8-week, studies: two studies in nonresponders to amlodipine (data pooled for amlodipine), two studies on nonresponders to telmisartan (pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Not much information regarding the formulations is available as the studies are more clinically oriented and the combinations have been discussed with respect to their clinical outcomes only in majority of the cases. The drugs most commonly employed in combination with AD (i.e., single drug + AD combination) include aliskiren [3941], atorvastatin [4252], azilsartan [53], benazepril [54, 55], fimasartan [56], indapamide [57, 58], irbesartan [59], olmesartan (olmesartan medoxomil) [39, 6067], perindopril [68–72], telmisartan [7377], and valsartan [70, 71, 7897]. …”
Section: Formulations Of Admentioning
confidence: 99%
“…Not much information regarding the formulations is available as the studies are more clinically oriented and the combinations have been discussed with respect to their clinical outcomes only in majority of the cases. The drugs most commonly employed in combination with AD (i.e., single drug + AD combination) include aliskiren [3941], atorvastatin [4252], azilsartan [53], benazepril [54, 55], fimasartan [56], indapamide [57, 58], irbesartan [59], olmesartan (olmesartan medoxomil) [39, 6067], perindopril [68–72], telmisartan [7377], and valsartan [70, 71, 7897]. …”
Section: Formulations Of Admentioning
confidence: 99%
“…Hu et al prepared a novel aqueous hydrolyzed polyacrylamide-based SiO 2 nanosuspension for EOR, and its rheological properties were investigated under different salinities and temperatures . Zhu et al formulated a polymer-grafted nanoparticle suspension by grafting a novel vinyltriethoxysilane-functionalized SiO 2 onto acrylamide (AM)/acrylic acid copolymer with the aim of obtaining a polymeric nanofluid with temperature and salt tolerance . Alaskar et al investigated the flow of polymeric nanoparticles through porous and fractured media and found that particle size, particle size distribution, shape, and surface charge were the main parameters affecting the transportation of polymeric nanoparticles through the porous media .…”
Section: Introductionmentioning
confidence: 99%
“…30 Zhu et al formulated a polymer-grafted nanoparticle suspension by grafting a novel vinyltriethoxysilane-functionalized SiO 2 onto acrylamide (AM)/acrylic acid copolymer with the aim of obtaining a polymeric nanofluid with temperature and salt tolerance. 31 Alaskar et al investigated the flow of polymeric nanoparticles through porous and fractured media and found that particle size, particle size distribution, shape, and surface charge were the main parameters affecting the transportation of polymeric nanoparticles through the porous media. 32 Liu et al performed rheological studies on a novel core−shell polymer-grafted nanoparticle synthesized from in situ free-radical polymerization-functionalized SiO 2 nanoparticle and acrylamide-based polymer molecules.…”
Section: Introductionmentioning
confidence: 99%